Detroit is our beat : tales of the four horsemen - Estleman, Loren D. (Tyrus Books, an imprint of F+W Media, Inc., 2015)
During World War II, while most of the Detroit police department is fighting overseas, the "Four Horsemen" -- Lieutenant Max Zagreb, Sergeant Starvo Canal, and Detectives McReary and Burke -- struggle to keep the city safe from draft-dodging troublemakers, gangsters, racial tension and enemy saboteurs.